2019
DOI: 10.22219/jpbi.v5i3.8842
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intention to act and knowledge of environmental issues on environmental behavior

Abstract: Intention to act and environmental issues knowledge has been assumed as the two variables which affect people’s environmental behavior. This study aimed at determining the correlations between variables (i.e. intention to act, environmental issues knowledge, and environmental behavior) on biology teachers in State High Schools of Pandeglang Regency. This survey research used quantitative approach. The sample was 51 teachers chosen using simple random sampling.  Meanwhile, the population was 61 teachers in Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
2
2
1
Order By: Relevance
“…Socially, the intention or desire to act is the influence of the community's view that the individual needs to take action in this case, namely ecological behavior. This is in line with several studies which state a strong relationship between the desire to act and ecological behavior (Bamberg & Möser, 2007;Fibula Purnama et al, 2020;Iman et al, 2019).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Socially, the intention or desire to act is the influence of the community's view that the individual needs to take action in this case, namely ecological behavior. This is in line with several studies which state a strong relationship between the desire to act and ecological behavior (Bamberg & Möser, 2007;Fibula Purnama et al, 2020;Iman et al, 2019).…”
Section: Resultssupporting
confidence: 90%
“…This happens because knowledge is one of the indirect experiences so that it is less able to encourage students' desire to act, especially in ecological behavior. In contrast to the results of previous studies which suggested that knowledge can affect the desire to act (Ajzen et al, 2011;Fielding & Head, 2012;Hasyim, 2013;Iman et al, 2019). The desire to act is the basic reason for a behavior.…”
Section: Resultscontrasting
confidence: 58%
“…The results indicate that the self-determined commitments undertaken by local economic agents is a factor that promotes the adoption of pro-environmental behavior. This is in line with theories and studies that assume intention as an internal variable that influences people's environmental behavior patterns (Ajzen, 1991(Ajzen, , 2011Prochaska and DiClemente, 1992;Farrow et al, 2017;Iman et al, 2019;Schill et al, 2019). The EIT Producer encourages self-determined commitments by local economic agents, representing a crucial methodological aspect for generating pro-environmental behavior.…”
Section: Discussionsupporting
confidence: 80%
“…These results are consistent with those of Lee et al (2021) in Pakistan. The results of another study on the ecological behavior of biology professors showed that their knowledge of environmental issues indirectly influences their behavior through the intention to act (Iman et al, 2019). This is measured by the desire to protect the environment.…”
Section: Environmental Behavior Changementioning
confidence: 99%
“…The degree to which individuals are knowledgeable and concerned about environmental problems, such as climate change, pollution, deforestation, and resource depletion, can be referred to as awareness of sustainable issues [51]. This awareness includes a comprehension of the potentially detrimental effects of human actions on the environment as well as the significance of sustainable behaviors [52].…”
Section: Awarenessmentioning
confidence: 99%